In-vivo time course of organ uptake and blood-brain-barrier permeation of poly(L-lactide) and poly(perfluorodecyl acrylate) nanoparticles with different surface properties in unharmed and brain-traumatized rats - Bechinger, Patrick; Serrano Sponton, Lucas; Grützner, Verena; Musyanovych, Anna; Jussen, Daniel; Krenzlin, Harald; Eldahaby, Daniela; Riede, Nicole; Kempski, Oliver; Ringel, Florian; Alessandri, Beat (Frontiers in Neurology, 2023)
Background: Traumatic brain injury (TBI) has a dramatic impact on mortality and quality of life and the development of effective treatment strategies is of great socio-economic relevance. A growing interest exists in using polymeric nanoparticles (NP) as carriers across the blood-brain barrier (BBB) for potentially effective drugs in TBI. However, the effect of NP material and type of surfactant on their distribution within organs, the amount of the administrated dose that reaches the brain parenchyma in areas with intact and opened BBB after trauma, and a possible elicited inflammatory response are still to be clarified. Methods: The organ distribution, BBB permeation and eventual inflammatory activation of polysorbate-80 (Tw80) and sodiumdodecylsulfate (SDS) stabilized poly(L-lactide) (PLLA) and poly(perfluorodecyl acrylate) (PFDL) nanoparticles were evaluated in rats after intravenous administration. The NP uptake into the brain was assessed under intact conditions and after controlled cortical impact (CCI). Results: A significantly higher NP uptake at 4 and 24 hours after injection was observed in the liver and spleen, followed by the brain and kidney, with minimal concentrations in the lungs and heart for all NP. A significant increase of NP uptake at 4 and 24 hours after CCI was observed within the traumatized hemisphere, especially in the perilesional area, but NP were still found in areas away from the injury site and the contralateral hemisphere. NP were internalized in brain capillary endothelial cells, neurons, astrocytes, and microglia. Immunohistochemical staining against GFAP, Iba1, TNFα, and IL1β demonstrated no glial activation or neuroinflammatory changes. Conclusions: Tw80 and SDS coated biodegradable PLLA and non-biodegradable PFDL NP reach the brain parenchyma with and without compromised BBB by TBI, even though a high amount of NP are retained in the liver and spleen. No inflammatory reaction is elicited by these NP within 24 hours after injection. Thus, these NP could be considered as potentially effective carriers or markers of newly developed drugs with low or even no BBB permeation.